EVALUATION OF THE LIPOLYTIC ACTIVITY OF FUNGUS ON CASTOR OIL (Ricinuscommunis) - Mendoza C., L. (2012)
The present study aims to select fungal strains having improved lipolytic activity in castor oil and see if its crude enzyme obtained by fermentation in liquid substrate (FSL) has the same activity on castor oil. Nine strains were isolated from fungi, Penicillium sp eight and one Aspergillus sp from waste vegetable oils. The results show that all studied strains of degradation halos developed, however, in no case was the halos of crude enzymatic degradation. The work showed that the strains of Penicillium sp and Aspergillus sp had a better cultural growth in castor oil and a good plate hydrolysis activity with short-chain triglyceride: tributirin.